Invasive mole presenting as pain abdomen - Singh, Swati; Kaur, Navdeep; Joshi, Swapan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Gestational trophoblastic neoplasms (GTN) are proliferative as well as degenerative disorders of placental elements and include complete or partial mole (90%), invasive mole (5.8%), choriocarcinoma (1-2%) and placental site tumor (1-2%). 15% of complete mole can develop into invasive mole. Very rarely (2-4%) partial mole can develop into invasive one presenting with features of incomplete abortion, mixed abortion and sometimes as obstetric emergencies like intraperitoneal hemorrhage. So, proper diagnosis and timely intervention can prevent mortality and reduce the morbidity of the patients.